Use of different leguminous seeds for lactating goats. Amino acid composition of the raw material and the rumen undegradable fraction - Ramos E.; Molina Alcaide E.; Yáñez Ruiz D.R.; Fernández J.R.; Sanz Sampelayo M.R. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The suitability of different leguminous seeds (lupine, beans, bitter vetch and vetch) for the nutrition of goats was investigated. The ruminal degradability of the N in each protein source was estimated using the nylon bag technique. The amino acid composition of the original protein sources and of the residues in the bags after ruminal incubation was also determined. The beans had more (P<0.05) of the quickly degradable fraction of crude protein than did the other three leguminous seeds. Lupine seeds had a higher (P<0.05) rate of degradation than did the other protein sources. The lowest value for effective degradability was observed for bitter vetch. The overall change in the amino acid profile due to ruminal fermentation depended on the protein source provided. The amino acid profile of the different leguminous seeds was among them, more similar before ruminal fermentation. However, the profile of their rumen undegradable protein fractions resulted very different. When a multivariate analysis was carried out, organization of the leguminous seeds in the order of the intensity of change, yielded the following: lupine, beans, bitter vetch and vetch.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)